Proposta de um sistema de aprendizagem à luz da abordagem experiencial: um estudo em cursos de mestrado profissional na área de Administração - Bispo, Ana Carolina Kruta de Araújo (2015)
As its main objective, this thesis aimed to propose a learning system based on an experiential approach in order to contribute to the training of professional master’s in Management. Specific objectives were outlined, which were then fulfilled throughout three distinct, but interconnected, steps. The first objective sought to define the dimensions that incorporate a learning system in professional master’s courses (PMC). To this end, an exploratory stage was conducted, with the participation of graduate coordinators, former graduate coordinators and people connected to the Capes board of directors. The results of this stage led to the delimitation of four macro procedural dimensions: historical-legal, socio-cultural, economic and political. Additionally, they indicated fundamental elements towards the delimitation of four micro procedural dimensions, linked to theoretical aspects of experiential learning: learning environment, theoretical and methodological knowledge, professional and social experiences and reflective practice. The second objective sought to identify the process of training of master’s students based on the perception of teachers and PMC managers in Business Administration considering the micro procedural dimensions. This second stage was carried out by the application of an online and open-ended questionnaire, which revealed the importance of the four micro procedural dimensions in the training processes of the professional master’s students, the presence of experiential learning in each, and the strengthening of the linkages between them. To understand the implications of the proposed dimensions in the process of training of professional master’s students and to identify the importance of active teaching methodologies for PMC, corresponding to the third and fourth goals of the research, interviews with graduate coordinators and former graduate coordinators of PMC that reached concepts of 4 and/or 5 in the 2010-2012 triennial evaluation of Capes, were conducted. From the results, it was possible to reflect on the elements that comprise the system, the dimensions, allowing for adjustments in its configuration. Thus, five macro procedural dimensions: legal, social, political, economic and legitimacy; and four micro procedural dimensions: learning environment, theoretical, methodological and technological knowledge, professional experience and reflective practice; have been characterized. The existence of an institutional environment that influences the macro and micro procedural dimensions that needs to be observed by those who conduct the PMC has also been found. Thus, the learning system marked by the experiential approach and influenced by an institutional environment, as well as the training process marked by experiential learning, constitute the theoretical contribution of this thesis. Managers and PMC teachers will be able to reflect on the proposed learning system and this, in turn, may be able to assist them in the development of new PMC, or even to assist existing ones in finding their differentiation from academic master's courses (AMC), to improve its training process through the reworking of their curricula, as well as the change in training processes for more efficient use of student experience and the development of a reflective practice; aspects that reveal the practical contribution of this thesis. It also features a social contribution, since the study enabled the development of management skills aimed at social interests, contributing effectively to the concentration area of the Doctorate in Management of the PPGA/UFPB. Thus, from the proposed learning system it is possible to institutionalize a process of natural training in PMC, which contributes on the framing of an identity for these courses.